DESCRIPTION OF BARRIERS TO ORAL HEALTH SERVICE ACCESS AMONG ELDERLY IN A SOCIAL INSTITUTION - Intan batura Endo Mahata; Sabrina Puti Humaira; Resa Ferdina; Leny Sang Surya (Fakultas Kedokteran Gigi Unjani, 2026)
Older adults living in social care institutions are at risk of oral and dental health problems due to physical limitations, dependence on the institution for support and limited access to professional dental care. The Sabai Nan Aluih Elderly Social Institution Sicincin, has no routine integration of dental services into institutional health care, which may create barriers to access. This study aimed to describe barriers to dental and oral healthcare based on the five dimensions of access by Penchansky and Thomas: availability, accessibility, accommodation, affordability, and acceptability. A descriptive quantitative cross-sectional study was conducted in November 2025 involving 51 older adults selected through total sampling. Data were collected using structured questionnaires and analyzed using frequency and percentage distributions. The most significant barrier was in the availability dimension, with no dentists in the institution (100%). Accessibility barriers included mobility and transportation difficulties (58.8%) despite 64.7% perceiving healthcare as easy to reach. Accommodation barriers were long waiting times (58.8%), and affordability barriers persisted even with health insurance (54.9%). Acceptability was not a significant barrier, with high comfort and trust in services (≥90%). These findings indicate multidimensional barriers, particularly in availability and accessibility, highlighting the need for integration of dental services in institutional care to improve oral health and quality of life for older adults. DOI : 10.54052/jhds.v6n1.p39-52